Antileukemic properties of spermacoce species - Sukari, Mohd Aspollah; Utami, Rahayu; Neoh, Bee Keat; Ee, Gwendoline Cheng Lian; Jusoh, Shokri; Mohd Nor, Siti Mariam; Rahmani, Mawardi (Chemic Publishing Company, 2013)
Antileukemic activity of th extracts and isolated compound from Spermacoce articularis, Spermacoce exilis and Spermacoce latifolia were carried out. All extracts of Spermacoce articularis as well as dichloromethane and ethyl acetate extracts of Spermacoce exilis showed strong activity against HL-60 cancer cell with IC50 value ranging from 0.4 to 7.2 μg/mL, whereas hexane extract of Spermacoce latifolia gave moderate activity with IC50 value of 13 ± 0.19 μg/mL. Ursolic acid as the major isolated constituent of these plants was found to have strong activity with IC50 of 1.3 ± 0.03 μg/mL against the same cancer cell.